Food security assessment of smallholder households based on resilience capacity index (RCI) in Gondang District, Mojokerto Regency - Riska Dwi Lutfianti; Elys Fauziyah; Fuad Hasan (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2026)
Food security has a crucial role in maintaining the sustainability of smallholder households that are vulnerable to climate and economic shocks. This study aims to describe the food security conditions of smallholder households, measure the level of food security, and formulate strategies to increase food security in smallholder households in Gondang District, Mojokerto Regency. The study used a quantitative descriptive method, with 43 respondents determined by purposive sampling. Food security level measurement was conducted using the Resilience Capacity Index (RCI). The results of the study show that the level of food security of smallholder households is in the very vulnerable category (RCI index was 34.66%). These conditions reflect limited adaptive capacity, assets, access to basic services and social safety nets. Food security for smallholder households can be achieved through an integrated approach that includes increasing the adaptive capacity of farmers, optimizing and diversifying productive assets, equitable access to basic services, and strengthening social safety nets.